A construção social do tipo "jogador de futebol profissional": um estudo sobre os repertórios usados por jogadores de distintas categorias etárias e por integrantes de suas matrizes - Pereira, Adriana Bernardes (2008)
Given the great variety of possibilities that the sports phenomenon in general presents to society, and specifically soccer in Brazilian society, we have chosen to study the collective construction of the type professional soccer player . Through a systematization of spoken and observed elements in soccer it was possible to reflect on the social configuration that permeates this construction and to understand the specifying matrixes, the social networks that are formed, the actors involved, the materialities that are present, the occurrence of competitions for strength in the social network, their characterization, and the interweavings of inter and intracategories in soccer. To make all this possible, we observed in loco the trainings and matches of different categories of soccer (3-5 year-olds, 6-8 year-olds, 9-11 year-olds, 12-16 year-olds, 17-20 year-olds, professionals). Also, we held informal conversations with players of these categories and the people they mentioned as part of their social networks (family members, professionals associated to soccer, such as physicians, nutritionists, physical therapists, journalists, teachers, coordinators, directors, and club sponsors). We decided to approach the age group/category in a crosssectional perspective, for which at least one soccer player of each category was randomly chosen to permit the identification of the social network that constitutes his universe as a soccer player. We observed their training and participation in matches, their routine, and the people present in their life when soccer is the issue. The question What is the meaning of being a professional soccer player? was the starting point for informal conversations with the components of the network, which demonstrated the meanings according to the point of view of each person involved in the construction of the professional soccer player type. The results showed that the trajectory of these young boys, searching for their formation and consolidation of their sense of belonging to this category, is defined by these meanings; as a result, they consolidate the matrix in which the type is updated as a category. The trajectory of these individuals is permeated by people and different situations, which produce their own ideas and expectations, not always correlated to the understanding of the reality the athletes live and want. To understand this trajectory, from the athlete s childhood to retirement, it was necessary to grasp the particularities and the psychosocial mediations of the construction of the professional soccer player type